Titration of Cholera Antitoxin in Human Sera by Microhemagglutination with Formalinized Erythrocytes - Hochstein, H. Donald (1970)
Microtiter hemagglutination tests employing formalinized sheep erythrocytes sensitized with either crude or purified cholera toxin were used to assay the cholera antitoxin content of human sera. Comparable results were obtained with either crude or purified toxin-sensitized cells with the exception of two sera that gave unusually high hemagglutination titers with the crude toxin. Sera from 13 convalescent cholera patients showed a high degree of correlation between antitoxin levels as determined in vitro by the hemagglutination test and in vivo by the skin permeability factor neutralization test. Fourfold or greater rises in antitoxin levels between acute and convalescent sera were detected in 9 of 15 patients with bacteriologically proven cholera. No significant increases in titer were observed in 14 cases of noncholera diarrhea. Cholera antitoxin was detected by hemagglutination in only 1 of 33 sera, obtained from eight countries, containing vibriocidal antibodies. Formalinized sheep erythrocytes sensitized with toxin and stored at 4 C in the presence of 1:10,000 thimerosal were stable and sensitive for at least 6 months (the longest time tested).